Analysis of Salary, Working Conditions, and Coworkers on Employee Job Satisfaction at Pt AlvaMountindo Medan - Rizal Ahmad (Institute of Computer Science (IOCS), 2022)
This study aims to find out how the influence of Salary (X1), Working Conditions (X2), and Coworkers (X3) on Job Satisfaction (Y) of employees of PT Alva Mountindo Medan. The population in this study were all employees of PT Alva Mountindo, totaling 94 employees. The number of samples taken by the population is 94 respondents. This research was conducted from December 2020 to February 2021. This study uses quantitative data processed by SPSS version 25.0 with multiple linear regression models. Sources of data come from respondents who were collected through questionnaires. The results showed that salary, working conditions, and colleagues had a positive and significant effect on PT Alva Mountindo's job satisfaction both partially and simultaneously. The salary variable is the most dominant variable influencing employee job satisfaction. 72.3% of employee job satisfaction can be explained and obtained from salary, working conditions, and co-workers, while the rest is from other factors. Employee job satisfaction has a very strong relationship to salary, working conditions, and colleagues.